2017
DOI: 10.1038/s41467-017-01744-5
|View full text |Cite
|
Sign up to set email alerts
|

A post-transcriptional program coordinated by CSDE1 prevents intrinsic neural differentiation of human embryonic stem cells

Abstract: While the transcriptional network of human embryonic stem cells (hESCs) has been extensively studied, relatively little is known about how post-transcriptional modulations determine hESC function. RNA-binding proteins play central roles in RNA regulation, including translation and turnover. Here we show that the RNA-binding protein CSDE1 (cold shock domain containing E1) is highly expressed in hESCs to maintain their undifferentiated state and prevent default neural fate. Notably, loss of CSDE1 accelerates neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 70 publications
0
47
0
Order By: Relevance
“…3f ). At the pluripotent state, hESCs express marginal amounts of PAX6 63 making these results difficult to interpret. Nevertheless, a decrease in PAX6 levels at the hESC stage could indicate a dysfunction in their ability to differentiate into NPCs.…”
Section: Resultsmentioning
confidence: 99%
“…3f ). At the pluripotent state, hESCs express marginal amounts of PAX6 63 making these results difficult to interpret. Nevertheless, a decrease in PAX6 levels at the hESC stage could indicate a dysfunction in their ability to differentiate into NPCs.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, UNR is a major node in a melanoma regulon, where it is thought to regulate over 60% of the transcripts considered to be involved in development of this malignancy. Additionally, UNR is highly expressed in human embryonic stem cells where it coordinatively regulates multiple nodes of networks essential for maintaining pluripotency ( Ju Lee et al, 2017 ). UNR stimulates the translation of RAC1 (Ras-related C3 botulinum toxin substrate 1, guanosine triphospatase belonging to the Ras superfamily), VIM (Vimentin, component of intermediate filaments important for mechanical integrity of cells during invasion, and also marker of epithelial-to-mesenchymal transition) and TRIO (Rho guanine nucleotide exchange factor which activates RAC1, implicated in uveal melanoma), and increases the stability of SDC4 ( trans -membrane receptor which activates RAC1 to transduce signals from extracellular matrix to the cytoskeleton and modulate adhesion and migration), TNC (extracellular matrix protein which interacts with SDC4 and is involved in regulation of cell adhesion) and CTTN (Cortactin, actin binding protein, implicated in tumor cell invasion and metastasis).…”
Section: Upstream Of N-ras Unrmentioning
confidence: 99%
“…The generation of Unr knockout mice demonstrated that, like Ybx1 , it is essential for mouse development. Further characterization demonstrated that Unr maintains the pluripotent state of embryonic stem cells [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%